Additive manufacturing for solid oxide cell electrode fabrication - Lomberg,M; Boldrin,P; Tariq,F; Offer,G; Wu,B; Brandon,NP (Electrochemical Society, 2015)
Additive manufacturing can potentially offer a highly-defined electrode microstructure, as well as fast and reproducible electrode fabrication. Selective laser sintering is an additive manufacturing technique in which three-dimensional structures are created by bonding subsequent layers of powder using a laser. Although selective laser sintering can be applied to a wide range of materials, including metals and ceramics, the scientific and technical aspects of the manufacturing parameters and their impact on microstructural evolution during the process are not well understood. In the present study, a novel approach for electrode fabrication using selective laser sintering was evaluated by conducting a proof of concept study. A Ni-patterned fuel electrode was laser sintered on an yttria-stabilized zirconia substrate. The optimization process of laser parameters (laser sintering rate and laser power) and the electrochemical results of a full cell with a laser sintered electrode are presented. The challenges and prospects of using selective laser sintering for solid oxide cell fabrication are discussed.